Prevalence of mastitis in Algerian dromedary camels and antimicrobial resistance of the causative Staphylococci - Imane Barka; Madjid Akkou; Djamel Khelef; Lamia Bentayeb; Amina Bouchami; Abdelkarim Boudrissa; Bernard Faye; Khatima Ait-Oudhia (Mljekarstvo)
To investigate the prevalence, bacterial spectrum of mastitis, and antimicrobial resistance of the causative staphylococci in Algerian dromedary camels, a total of 200 lactating camels were first examined for clinical mastitis and the healthy quarters were examined for subclinical mastitis using the California Mastitis Test (CMT). Milk samples from the affected quarters were collected aseptically and analysed using conventional bacteriological isolation and identification procedures. Staphylococcal isolates were then analysed for antimicrobial resistance. The overall prevalence of mastitis in camels based on CMT and clinical examination was 35 % (70/200), of which 7.5 % (15/200) was clinical mastitis and 27.5 % (55/200) was subclinical mastitis. At the quarterly level, the overall prevalence was 11.87 % (95/800), of which 2.62 % (21/800) was clinical mastitis and 9.25 % (74/800) was subclinical mastitis. A total of 98 bacterial isolates were identified from the 95 cultured milk samples. Staphylococci (70.4%) were the predominant isolates, with 31.63 % identified as coagulase-positive staphylococci (CPS) including S. aureus at 25.51 % and 38.77 % identified as coagulase-negative staphylococci (CNS). The remaining isolates were Micrococcus sp., Streptococcus sp., Bacillus sp., E. coli, and Enterococcus. Antibiotic susceptibility testing revealed that 24 (34.78 %) of the isolates were susceptible to all antimicrobial drugs tested, while 21.73 % (15/69) were multidrug resistant strains. The highest resistance rates were found for penicillin, tetracycline and erythromycin with 33.33 %, 31.48 % and 21.74 %, respectively. Therefore, the implementation of integrated approaches in the study is of great importance for the prevention and control of mastitis to improve the quality of camel milk, minimize economic losses and avoid significant public health risks.